Clinical evolution of epileptic seizures in children with perinatal brain pathology - E. A. Morozova; D. V. Morozov; V. A. Karlov (Неврология, нейропсихиатрия, психосоматика, 2013)
The complex mechanism of epileptogenesis has not been adequately explored. Perinatal brain pathology is one of the most important triggers of epilepsy in children. The paper gives data on the course and transformation of epileptic seizures in children who have verified perinatal problems. A study of 66 children with perinatally induced epileptic seizures has provided evidence for the evolution of impairments in cerebral hemodynamics and neuroimaging phenomena in the examined contingent of patients.